Biotechnological Production of Caffeic Acid by Bacterial Cytochrome P450 CYP199A2 - Furuya, Toshiki (American Society for Microbiology, 2012)
Caffeic acid is a biologically active molecule that has various beneficial properties, including antioxidant, anticancer, and anti-inflammatory activities. In this study, we explored the catalytic potential of a bacterial cytochrome P450, CYP199A2, for the biotechnological production of caffeic acid. When the CYP199A2 enzyme was reacted with p-coumaric acid, it stoichiometrically produced caffeic acid. The crystal structure of CYP199A2 shows that Phe at position 185 is situated directly above, and only 6.35 Å from, the heme iron. This F185 residue was replaced with hydrophobic or hydroxylated amino acids using site-directed mutagenesis to create mutants with novel and improved catalytic properties. In whole-cell assays with the known substrate of CYP199A2, 2-naphthoic acid, only the wild-type enzyme hydroxylated 2-naphthoic acid at the C-7 and C-8 positions, whereas all of the active F185 mutants exhibited a preference for C-5 hydroxylation. Interestingly, several F185 mutants (F185V, F185L, F185I, F185G, and F185A mutants) also acquired the ability to hydroxylate cinnamic acid, which was not hydroxylated by the wild-type enzyme. These results demonstrate that F185 is an important residue that controls the regioselectivity and the substrate specificity of CYP199A2. Furthermore, Escherichia coli cells expressing the F185L mutant exhibited 5.5 times higher hydroxylation activity for p-coumaric acid than those expressing the wild-type enzyme. By using the F185L whole-cell catalyst, the production of caffeic acid reached 15 mM (2.8 g/liter), which is the highest level so far attained in biotechnological production of this compound.